Correlation Of Educational Level And Age Of Pregnant Women On Triple Elimination Examination In Sentul Health Center Working Area Bogor District In 2023 - Dina, Dina Mariana Br Maha; Syarini, Syarini Novita; Alifani, Alifani Faiz Faradhila (International Journal of Midwifery and Health Sciences, 2024)
Background: According to the 2020 Indonesia Health Profile, more than 90% of children contract HIV, Syphilis, and Hepatitis B infections from their mothers. Triple elimination is a program that aims to achieve and maintain mother-to-child elimination of HIV/AIDS, Hepatitis B, and Syphilis. Method: This study, which is of significant importance, aims to determine the correlation between the educational level and age of pregnant women on triple elimination examinations in the work area of the Sentul Health Center, Bogor Regency, in 2023. This research uses a quantitative analytical research design. The population of this study is all pregnant women in the work area of the Sentul Health Center, Bogor Regency, for the month. December 2023, a total of 50 people used a sampling technique, namely total sampling. Result: The results of this study were based on the chi-square test, namely that there was a significant correlation between the level of education of pregnant women and the triple elimination examination, the p-value was 0.001 <α value (0.05), and there was a significant correlation between the age of the pregnant mother and the triple elimination examination, the value was obtained a p-value of 0.001 <α value (0.05). Suggestions: Providing knowledge and information about triple elimination examinations for pregnant women is recommended.